Association of Respiratory Mechanic Instability and Respiratory Parameters among Adults with Obstructive Sleep Apnea. (May 2019) - Choi, Ji Ho; Lee, Bora; Hwang, Se-Hwan
Objectives: Respiratory mechanic instability (RMI) is derived from analysis of paradoxical thoracoabdominal movements during airway obstruction. This study aimed to evaluate RMI parameters in obstructive sleep apnea (OSA) and the correlation between RMI parameters and other parameters in polysomnography. Study Design: Retrospective review. Setting: A university hospital. Methods: A retrospective chart review was performed, and data from 189 adult patients who underwent an in-laboratory sleep study and were seen in our clinic during the past 8 months. The RMI parameters were measured from thoracoabdominal bands during polysomnography. Results: Subjects were divided into 2 groups: control (n = 67, apnea-hypopnea index [AHI] <5) and OSA (n = 122, AHI ≥5). The OSA group was divided into 3 subgroups according to AHI: mild, 5 ≤ AHI < 15; moderate, 15 ≤ AHI < 30; severe, AHI ≥30. As AHI increased, all RMI parameters showed a significant rising pattern and difference between control and subgroups. Arousal index, lowest oxygen saturation, and oxygen desaturation index ≥3% were significantly correlated with all RMI parameters. Based on cutoff values, areas under the curves of the RMI index for predicting mild, moderate, and severe OSA were >0.85. Conclusion: All RMI parameters were well related to respiratory parameters of polysomnography, such as arousal index, lowest oxygen saturation, and oxygen desaturation index ≥3%. The areas under the curves of all RMI parameters for predicting OSA and subgroups showed significant diagnostic performance. These parameters may be useful to identify OSA cases from control.